Social and Speech Portraits of Social Groups in Tatar Society in the Second Half 19th and Early 20th Centuries: A Value-Axiological and Stylistic Perspective - Mirkhayev, Rifat F.; Minnullin, Bakhtiyar K. (The New Research of Tuva, 2025)
This article examines the social and speech portraits of the main social groups within Tatar society in the second half of the 19th and the early 20th centuries from value-axiological and stylistic perspectives. The relevance of this study stems from the need to address the issue of examining the social foundations of linguistic processes in their historical dimension, particularly the communicative practices of the subjects engaged in social relations. According to the authors, it is within this communicative activity that the mechanisms of language development originate and are set in motion. The study reveals that during this period, in addition to the peasantry, the social structure of Tatar society included representatives of commercial circles, religious and educational communities, as well as ordinary townspeople. The social and speech characteristics of these groups were largely determined by utilitarian value and axiological orientations. The social and speech portraits of these social groups are marked by the dominance of colloquial style elements, while the use of literary language resources remained minimal. This observation indicates that, amid the social transformations that occurred within Tatar society during this period, colloquial forms of the Tatar language became the most accessible and widely demanded means of social communication.